Ben Franklin's big splash : the mostly true story of his first invention - Rosenstock, Barb; Schindler, S. D. (New York : Scholastic, 2014)
"Ben Franklin loved to swim and, at the age of eleven, he was determined to swim like a fish--fins and all. This ... account of young Ben's earliest invention follows the budding scientist's journey as he tests and retests his swim fins. That first big splash led Ben to even more innovations and inventions. Includes Franklin quotes, a timeline, bibliography, and source notes"--
Includes bibliographical references.
Keywords: Franklin, Benjamin, -- 1706-1790 -- Childhood and youth -- Juvenile fiction; Franklin, Benjamin, -- 1706-1790 -- Childhood and youth -- Fiction; Inventors -- Juvenile fiction; Inventions -- Juvenile fiction; Swimming -- Juvenile fiction; Inventors -- Fiction; Inventions -- Fiction; Swimming -- Fiction